The social impact analysis of "Rise a Voice, Airlangga Got Talent" program with social return on investment approach - Zalfa Karina; Gancar Candra Premananto (Journal of Community Service and Empowerment, 2024)
This study aimed to evaluate and calculate the social impact value from the "Rise A Voice, Airlangga Got Talent" Program. The program was a Creating Share Value activity carried out by Master of Management students at Airlangga University for orphanages in Surabaya. It was held to provide a platform for the orphanage children's creations and direction related to good orphanage management. However, after the implementation of the program, there were no measurement results related to the social impact received. Therefore, this research was conducted to calculate the value of the social impact using the Social Return on Investment (SROI) approach as a research method. The result showed that the Program produced an SROI value of 36.04. It can be inferred that every 1 Rupiah invested in the "Rise A Voice, Airlangga Got Talent" Program was able to generate return of Rp. 36.04. Meanwhile, the payback period can be gained in 1.7 months. This program can be categorized as successful because it is able to exceed a ratio of 1 in SROI. The calculation of SROI is important to evaluate and develop strategies for the program sustainability as an illustration for investors who are willing to invest in the same program.